Penguatan Karakter Peserta Didik yang Moderat melalui Pembelajaran Matematika - Rustanuarsi, Ressy (Social, Humanities, and Educational Studies (SHES): Conference Series, 2025)
The growing issues of intolerance and radicalism have prompted the government to adopt religious moderation as a strategic response involving various sectors, including education in schools and madrasahs. This study aims to analyze strategies for strengthening students’ moderate character through mathematics learning. The research employs a library research method, with the object of study consisting of relevant literature such as books, scholarly articles, and policy documents related to the topic. The researcher serves as the primary instrument, supported by data cards used to record key findings from the literature analysis. The data analysis technique applied is content analysis. The findings reveal several strategies that can be implemented to foster students’ moderate character, including: (1) Embedding Pancasila values into mathematics content to reinforce national commitment; (2) Applying relevant instructional models and integrating the value of tolerance into mathematics lessons to cultivate a tolerant attitude; (3) Fostering mutual respect by encouraging openness to differing opinions and promoting positive social interactions to prevent radicalism and violence; and (4) Implementing ethnomathematics-based learning to develop an accommodative attitude toward local cultures.  Thus, strengthening moderate character can be achieved through relevant pedagogical approaches and the contextual integration of religious moderation values into mathematics learning.Meningkatnya isu intoleransi dan radikalisme mendorong pemerintah menetapkan moderasi beragama sebagai respons strategis yang melibatkan berbagai elemen, termasuk pendidikan di sekolah dan madrasah. Penelitian ini bertujuan untuk menganalisis strategi penguatan karakter peserta didik yang moderat melalui pembelajaran matematika. Penelitian ini menggunakan metode studi kepustakaan (library research). Objek penelitian ini adalah literatur yang relevan, seperti buku, artikel ilmiah, dan dokumen kebijakan yang berkaitan dengan topik kajian. Peneliti berperan sebagai instrumen utama, dibantu kartu data untuk mencatat temuan penting dari analisis literatur. Teknik analisis data yang digunakan adalah analisis isi (content analysis). Hasil kajian menunjukkan bahwa terdapat beberapa strategi yang dapat diimplementasikan untuk membentuk karakter moderat peserta didik, antara lain: (1) Menyisipkan nilai-nilai Pancasila dalam materi matematika guna memperkuat komitmen kebangsaan; (2) Menerapkan model pembelajaran yang relevan dan mengintegrasikan nilai toleransi kedalam materi matematika guna menumbuhkan sikap toleransi; (3) Membiasakan sikap saling menghormati dengan menghargai perbedaan pendapat dan menciptakan interaksi sosial positif untuk mencegah radikalisme dan kekerasan; serta (4) Menerapkan pembelajaran bermuatan etnomatematika untuk menumbuhkan sikap akomodatif terhadap budaya lokal. Dengan demikian, penguatan karakter moderat dapat diwujudkan melalui pendekatan pedagogis yang relevan serta integrasi nilai-nilai moderasi beragama ke dalam pembelajaran matematika secara kontekstual.